Non-native autoinducer analogs capable of modulating the SdiA quorum sensing receptor in Salmonella enterica serovar Typhimurium - Styles, Matthew J.; Blackwell, Helen E. (Beilstein Journal of Organic Chemistry, 2018)
Quorum sensing (QS) allows many common bacterial pathogens to coordinate group behaviors such as virulence factor production, host colonization, and biofilm formation at high population densities. This cell–cell signaling process is regulated by N-acyl L-homoserine lactone (AHL) signals, or autoinducers, and LuxR-type receptors in Gram-negative bacteria. SdiA is an orphan LuxR-type receptor found in Escherichia, Salmonella, Klebsiella, and Enterobacter genera that responds to AHL signals produced by other species and regulates genes involved in several aspects of host colonization. The inhibition of QS using non-native small molecules that target LuxR-type receptors offers a non-biocidal approach for studying, and potentially controlling, virulence in these bacteria. To date, few studies have characterized the features of AHLs and other small molecules capable of SdiA agonism, and no SdiA antagonists have been reported. Herein, we report the screening of a set of AHL analogs to both uncover agonists and antagonists of SdiA and to start to delineate structure–activity relationships (SARs) for SdiA:AHL interactions. Using a cell-based reporter of SdiA in Salmonella enterica serovar Typhimurium, several non-natural SdiA agonists and the first set of SdiA antagonists were identified and characterized. These compounds represent new chemical probes for exploring the mechanisms by which SdiA functions during infection and its role in interspecies interactions. Moreover, as SdiA is highly stable when produced in vitro, these compounds could advance fundamental studies of LuxR-type receptor:ligand interactions that engender both agonism and antagonism.
Keywords: N-acyl L-homoserine lactone; LuxR-type receptor; Quorum sensing; Salmonella enterica serovar Typhimurium; SdiA

(untitled) - Wright, G. D. (Nat. Rev. Microbiol., 2007)

Antibiotic Resistance. Handbook of Experimental Pharmacology - Wright, G. D. (The Origins of Antibiotic Resistance, 2012)

(untitled) - Bush, K.; Courvalin, P.; Dantas, G.; Davies, J.; Eisenstein, B.; Huovinen, P.; Jacoby, G. A.; Kishony, R.; Kreiswirth, B. N.; Kutter, E.; Lerner, S. A.; Levy, S.; et al. (Nat. Rev. Microbiol., 2011)

(untitled) - Clatworthy, A. E.; Pierson, E.; Hung, D. T. (Nat. Chem. Biol., 2007)

(untitled) - Maura, D.; Ballok, A. E.; Rahme, L. G. (Curr. Opin. Microbiol., 2016)

(untitled) - Cegelski, L.; Marshall, G. R.; Eldridge, G. R.; Hultgren, S. J. (Nat. Rev. Microbiol., 2008)

(untitled) - Whiteley, M.; Diggle, S. P.; Greenberg, E. P. (Nature, 2017)

(untitled) - Sintim, H. O.; Smith, J. A.; Wang, J.; Nakayama, S.; Yan, L. (Future Med. Chem., 2010)

(untitled) - Njoroge, J.; Sperandio, V. (EMBO Mol. Med., 2009)

(untitled) - Schuster, M.; Sexton, D. J.; Diggle, S. P.; Greenberg, E. P. (Annu. Rev. Microbiol., 2013)

(untitled) - Rutherford, S. T.; Bassler, B. L. (Cold Spring Harbor Perspect. Med., 2012)

(untitled) - Parker, C. T.; Sperandio, V. (Cell. Microbiol., 2009)

(untitled) - Waters, C. M.; Bassler, B. L. (Annu. Rev. Cell Dev. Biol., 2005)

(untitled) - Dyszel, J. L.; Soares, J. A.; Swearingen, M. C.; Lindsay, A.; Smith, J. N.; Ahmer, B. M. M. (PLoS One, 2010)

(untitled) - Venturi, V.; Ahmer, B. M. M. (Front. Cell. Infect. Microbiol., 2015)

(untitled) - Michael, B.; Smith, J. N.; Swift, S.; Heffron, F.; Ahmer, B. M. M. (J. Bacteriol., 2001)

(untitled) - Smith, J. N.; Dyszel, J. L.; Soares, J. A.; Ellermeier, C. D.; Altier, C.; Lawhon, S. D.; Adams, L. G.; Konjufca, V.; Curtiss, R., III; Slauch, J. M.; Ahmer, B. M. M. (PLoS One, 2008)

(untitled) - Dyszel, J. L.; Smith, J. N.; Lucas, D. E.; Soares, J. A.; Swearingen, M. C.; Vross, M. A.; Young, G. M.; Ahmer, B. M. M. (J. Bacteriol., 2010)

(untitled) - Habyarimana, F.; Sabag-Daigle, A.; Ahmer, B. M. M. (J. Bacteriol., 2014)

(untitled) - Janssens, J. C.; Metzger, K.; Daniels, R.; Ptacek, D.; Verhoeven, T.; Habel, L. W.; Vanderleyden, J.; De Vos, D. E.; De Keersmaecker, S. C. (Appl. Environ. Microbiol., 2007)

(untitled) - Kim, T.; Duong, T.; Wu, C. A.; Choi, J.; Lan, N.; Kang, S. W.; Lokanath, N. K.; Shin, D.; Hwang, H.-Y.; Kim, K. K. (Acta Crystallogr., Sect. D: Biol. Crystallogr., 2014)

(untitled) - Nguyen, Y.; Nguyen, N. X.; Rogers, J. L.; Liao, J.; MacMillan, J. B.; Jiang, Y.; Sperandio, V. (mBio, 2015)

(untitled) - Wang, X. D.; de Boer, P. A.; Rothfield, L. I. (EMBO J., 1991)

(untitled) - García-Lara, J.; Shang, L. H.; Rothfield, L. I. (J. Bacteriol., 1996)

(untitled) - Kanamaru, K.; Kanamaru, K.; Tatsuno, I.; Tobe, T.; Sasakawa, C. (Mol. Microbiol., 2000)

(untitled) - Ahmer, B. M. M.; van Reeuwijk, J.; Timmers, C. D.; Valentine, P. J.; Heffron, F. (J. Bacteriol., 1998)

(untitled) - Smith, J. N.; Ahmer, B. M. M. (J. Bacteriol., 2003)

(untitled) - Ahmer, B. M. M. (Mol. Microbiol., 2004)

(untitled) - Hughes, D. T.; Terekhova, D. A.; Liou, L.; Hovde, C. J.; Sahl, J. W.; Patankar, A. V.; Gonzalez, J. E.; Edrington, T. S.; Rasko, D. A.; Sperandio, V. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Van Houdt, R.; Aertsen, A.; Moons, P.; Vanoirbeek, K.; Michiels, C. W. (FEMS Microbiol. Lett., 2006)

(untitled) - Sharma, V. K.; Bearson, S. M. D.; Bearson, B. L. (Microbiology (London, U. K.), 2010)

(untitled) - Abed, N.; Grépinet, O.; Canepa, S.; Hurtado-Escobar, G. A.; Guichard, N.; Wiedemann, A.; Velge, P.; Virlogeux-Payant, I. (Mol. Microbiol., 2014)

(untitled) - Bouwman, C. W.; Kohli, M.; Killoran, A.; Touchie, G. A.; Kadner, R. J.; Martin, N. L. (J. Bacteriol., 2003)

(untitled) - Heffernan, E. J.; Wu, L.; Louie, J.; Okamoto, S.; Fierer, J.; Guiney, D. G. (Infect. Immun., 1994)

(untitled) - Rosselin, M.; Virlogeux-Payant, I.; Roy, C.; Bottreau, E.; Sizaret, P.-Y.; Mijouin, L.; Germon, P.; Caron, E.; Velge, P.; Wiedemann, A. (Cell Res., 2010)

(untitled) - Yang, Y.; Zhou, M.; Hardwidge, P. R.; Cui, H.; Zhu, G. (Front. Cell. Infect. Microbiol., 2018)

(untitled) - Yao, Y.; Martinez-Yamout, M. A.; Dickerson, T. J.; Brogan, A. P.; Wright, P. E.; Dyson, H. J. (J. Mol. Biol., 2006)

(untitled) - Welsh, M. A.; Blackwell, H. E. (FEMS Microbiol. Rev., 2016)

(untitled) - O'Connor, C. J.; Laraia, L.; Spring, D. R. (Chem. Soc. Rev., 2011)

(untitled) - Galloway, W. R. J. D.; Hodgkinson, J. T.; Bowden, S.; Welch, M.; Spring, D. R. (Trends Microbiol., 2012)

(untitled) - Morkunas, B.; Galloway, W. R. J. D.; Wright, M.; Ibbeson, B. M.; Hodgkinson, J. T.; O'Connell, K. M. G.; Bartolucci, N.; Della Valle, M.; Welch, M.; Spring, D. R. (Org. Biomol. Chem., 2012)

(untitled) - Hodgkinson, J. T.; Galloway, W. R. J. D.; Wright, M.; Mati, I. K.; Nicholson, R. L.; Welch, M.; Spring, D. R. (Org. Biomol. Chem., 2012)

(untitled) - Rabin, N.; Delago, A.; Inbal, B.; Krief, P.; Meijler, M. M. (Org. Biomol. Chem., 2013)

(untitled) - Amara, N.; Mashiach, R.; Amar, D.; Krief, P.; Spieser, S. A. H.; Bottomley, M. J.; Aharoni, A.; Meijler, M. M. (J. Am. Chem. Soc., 2009)

(untitled) - Geske, G. D.; O'Neill, J. C.; Miller, D. M.; Mattmann, M. E.; Blackwell, H. E. (J. Am. Chem. Soc., 2007)

(untitled) - Palmer, A. G.; Streng, E.; Blackwell, H. E. (ACS Chem. Biol., 2011)

(untitled) - Stacy, D. M.; Welsh, M. A.; Rather, P. N.; Blackwell, H. E. (ACS Chem. Biol., 2012)

(untitled) - Welsh, M. A.; Eibergen, N. R.; Moore, J. D.; Blackwell, H. E. (J. Am. Chem. Soc., 2015)

(untitled) - Welsh, M. A.; Blackwell, H. E. (Cell Chem. Biol., 2016)

(untitled) - O'Loughlin, C. T.; Miller, L. C.; Siryaporn, A.; Drescher, K.; Semmelhack, M. F.; Bassler, B. L. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Geske, G. D.; O’Neill, J. C.; Miller, D. M.; Wezeman, R. J.; Mattmann, M. E.; Lin, Q.; Blackwell, H. E. (ChemBioChem, 2008)

(untitled) - Geske, G. D.; Mattmann, M. E.; Blackwell, H. E. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - McInnis, C. E.; Blackwell, H. E. (Bioorg. Med. Chem., 2011)

(untitled) - McInnis, C. E.; Blackwell, H. E. (Bioorg. Med. Chem., 2011)

(untitled) - Gerdt, J. P.; Wittenwyler, D. M.; Combs, J. B.; Boursier, M. E.; Brummond, J. W.; Xu, H.; Blackwell, H. E. (ACS Chem. Biol., 2017)

(untitled) - Eibergen, N. R.; Moore, J. D.; Mattmann, M. E.; Blackwell, H. E. (ChemBioChem, 2015)

(untitled) - Mattmann, M. E.; Geske, G. D.; Worzalla, G. A.; Chandler, J. R.; Sappington, K. J.; Greenberg, E. P.; Blackwell, H. E. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Palmer, A. G.; Streng, E.; Jewell, K. A.; Blackwell, H. E. (ChemBioChem, 2011)

(untitled) - Moore, J. D.; Rossi, F. M.; Welsh, M. A.; Nyffeler, K. E.; Blackwell, H. E. (J. Am. Chem. Soc., 2015)

(untitled) - Lindsay, A.; Ahmer, B. M. M. (J. Bacteriol., 2005)

Experiments in Molecular Genetics - Miller, J. H. (Cold Spring Press, 1972)

(untitled) - Sabag-Daigle, A.; Ahmer, B. M. M. (PLoS One, 2012)

(untitled) - Mattmann, M. E.; Shipway, P. M.; Heth, N. J.; Blackwell, H. E. (ChemBioChem, 2011)

(untitled) - O'Reilly, M. C.; Dong, S.-H.; Rossi, F. M.; Karlen, K. M.; Kumar, R. S.; Nair, S. K.; Blackwell, H. E. (Cell Chem. Biol., 2018)

(untitled) - Lequette, Y.; Lee, J.-H.; Ledgham, F.; Lazdunski, A.; Greenberg, E. P. (J. Bacteriol., 2006)

(untitled) - Gerdt, J. P.; McInnis, C. E.; Schell, T. L.; Rossi, F. M.; Blackwell, H. E. (Chem. Biol., 2014)